2006
DOI: 10.1128/iai.00304-06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance ofPorphyromonas gingivalisto Killing by Serum Complement

Abstract: The complement system plays an important role in the host defense against infection, and the formation of the terminal complement complex on the bacterial surface has been shown to be particularly important in killing of gram-negative bacteria. The gram-negative periodontal pathogen Porphyromonas gingivalis is resistant to complement killing, and possible mechanisms suggested for this resistance include protease production and capsule formation. In this study, P. gingivalis Arg-and Lys-gingipain deletion mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 44 publications
(38 reference statements)
3
92
1
Order By: Relevance
“…The results of this study are in contrast with other published results that showed that a P. gingivalis mutant lacking all three gingipains was extremely sensitive to lysis by complement (30). In direct contrast, a mutant lacking HRgpA and RgpB was reported to survive in NHS equally well as the wild type (20) or to survive at 28% as compared with 87% for the wild type (30). It is unclear at the moment what the reason is for these discrepancies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The results of this study are in contrast with other published results that showed that a P. gingivalis mutant lacking all three gingipains was extremely sensitive to lysis by complement (30). In direct contrast, a mutant lacking HRgpA and RgpB was reported to survive in NHS equally well as the wild type (20) or to survive at 28% as compared with 87% for the wild type (30). It is unclear at the moment what the reason is for these discrepancies.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, we found that NHS preincubated with P. gingivalis wild-type strains also lost its bactericidal activity toward E. coli. A recent publication has shown that P. gingivalis lacking the gingipains HRgpA and RgpB or Kgp are indeed opsonized with larger amounts of C3b but that this does not lead to the lysis of bacteria (20). The authors suggest that lysis is prevented by the presence of anionic polysaccharides on a bacterial surface.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, P. gingivalis is very resistant to killing by complement; this is attributable to the ability of its gingipain proteases to degrade C3 and C5 and thereby prevent deposition of C3b on the bacterial cell surface, which moreover contains a complement-resistant anionic polysaccharide (Popadiak et al, 2007;Slaney et al, 2006). Intriguingly, degradation of C5 by P. gingivalis leads to generation of a biologically active C5a-like fragment (Wingrove et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…These loci are, therefore, probably involved in the biosynthesis of A-LPS [60,61]. Furthermore, the mutants were susceptible to killing by the complement system, suggesting that A-LPS has a role in serum resistance to P. gingivalis [61,62]. Also, in the non-pigmented P. gingivalis strain HG66, which lacks A-LPS but possesses O-LPS, a nonsense mutation in the wbpB gene was detected, and Wbp pathway gene mutants were found to be A-LPS deficient [60].…”
Section: A-lps Provides Serum Resistance To P Gingivalismentioning
confidence: 99%